INDIVIDUAL KINESITHERAPEUTIC APPROACH IN PATIENTS WITH TOTAL HIP REPLACEMENT - Gergana Nenova; Paraskeva Mancheva (Peytchinski Publishing, 2022)
The individual kinesitherapeutic approach is increasingly required in rehabilitation practice due to the presence of concomitant diseases, social problems and psycho-emotional characteristics of the patients. Its effectiveness can be assessed by examining the level of satisfaction of patients with total hip arthroplasty with the work of the kinesitherapist. Purpose: to study and evaluate the effectiveness of the individual kinesitherapeutic approach on patients with total hip arthroplasty. Material and methods: Material: 60 patients who have undergone operative intervention for total hip replacement at the Orthopaedics and Traumatology Clinic at the University Hospital St. Marina, Varna for the period 2012-2019. The patients are divided into experimental (30 patients with a mean age of 56.17) and control groups (30 patients with a mean age of 55.53). Methods: Sociological method (questionnaire survey): questionnaire for satisfaction with the kinesitherapist's work on the Likert scale (α-Cronbach 0.823); Statistical method: statistical data grouping, Cronbach's test, descriptive method, testing of statistical hypotheses, correlation analysis. The data is processed with SPSS v.19.0 for Windows. Results and discussion: 83,3% of patients with total hip replacement answered that they have received answers to their questions from the kinesitherapist treating them. The patients in the experimental and control groups were equally aware of the need for kinesitherapy in their postoperative recovery period. 100% of the respondents in the control group believed that the kinesitherapist was very interested and inquired about concomitant diseases and problems that arose during the procedures. Patients with custom hip replacement report greater freedom "to a very large extent" and 26,7% to a large extent. Conclusion: the application of the individual kinesitherapeutic approach to patients with total hip arthroplasty leads to a faster and fuller functional recovery and to a higher level of satisfaction.